GASTROESOPHAGEAL REFLUX DISEASE: ETIOLOGY, CLINICAL PRESENTATION, CLASSIFICATION, DIAGNOSIS, AND TREATMENT METHODS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2025)
Gastroesophageal reflux disease (GERD) is a chronic condition in which gastric and/or duodenal contents regularly flow back into the esophagus. This process is accompanied by heartburn, regurgitation, and retrosternal discomfort. Recurrent reflux episodes damage the mucosal lining of the distal esophagus and lead to esophagitis (an inflammation of the esophageal lining), while certain patients develop Barrett’s esophagus (intestinal metaplasia of the esophageal mucosa)